Aktuelle Anforderungen an das Bildmanagement in der Strahlentherapie - Steil, Volker; Schneider, Frank; Wenz, Frederik; Lohr, Frank; Weisser, Gerald (Strahlentherapie und Onkologie, 2012)
Aims and methods: Treatment techniques of increasing complexity such as dynamic/rotational techniques mandate digital management and increasingly image guidance. This constantly increases requirements for image management and archiving. This article discusses the current status of these requirements and will present potential image administration strategies. Results: Fundamentals of image administration and storage/archiving are presented (DICOM Standard, radiotherapy-specific issues) along the typical patient pathway (demographic data, radiotherapy treatment planning, signatures/approval of plan and image data, archiving of plan and image data). Different strategies for image management are presented (archiving centered on individual application vs. integral approach with central archiving in a DICOM-RT-PACS governed by a radiation oncology information system (ROCIS)). Infrastructural requirements depending on the amount of image data generated in the department are discussed. Conclusion: Application-centered image management provides access to image data including all relevant RT-specific elements. This approach, however, is not migration-safe, requires significant administrative work to ensure a redundancy level that protects against data loss and does not provide datasets that are linked to respective therapeutic interventions. Therefore, centralized image management and archiving that links images to patients and individual steps in the treatment pathway within a standardized DICOM(-RT) environment is preferable despite occasional problems with visualization of specific data elements.
Gesehen am 21.09.2018